The NS1 protein of contemporary West African Zika virus is efficient to increase cellular permissiveness to virus replication - (:unkn) unknown (My University, 2024)
Mosquito-borne Zika virus (ZIKV; orthoflavivirus, Flaviviridae) has become a global health problem due to expansion of the geographic distribution of Asian Lineage virus. Contemporary ZIKV strains of African lineage have recently gained increased attention due to their epidemic potential and their capacity to be highly teratogenic in humans. The ZIKV non-structural NS1 protein from recent West African strains Africa was been studied where with view of its importance in the pathogenicity. NS1 protein from contemporary West African ZIKV (NS1CWA) and historical African ZIKV strain MR766 (NS1MR766) differ by seven amino-acid substitutions. Expression of recombinant NS1 proteins showed differences in the subcellular distribution between NS1CWA and NS1MR766 in HEK-293T cells. There was an increased secretion efficiency of soluble NS1CWA compared to NS1MR766. The replication of a chimeric MR766/NS1CWA virus was studied in Vero and A549 cells. Insertion of NS1CWA into MR766 enhances virus replication in both cell lines leading to more pronounced cell death. This correlated with lower up-regulation of IFN-β and interferon-stimulated gene mRNA in A549 cells infected by MR766/NS1CWA virus. Our data raise the question on the importance of NS1 protein in the pathogenicity of contemporary ZIKV from West Africa, and point to differences within viral strains belonging to the same African lineage.
Keywords: African Research